Variable‐temperature structural studies on valence tautomerism in cobalt bis(dioxolene) molecular complexes. Issue 2 (1st April 2017) - Hathwar, Venkatesha R.; Stingaciu, Marian; Richter, Bo; Overgaard, Jacob; Iversen, Bo B.
Abstract : Thermal valence tautomerism in the cobalt‐bis(dioxolene) molecular complexes is evaluated using variable‐temperature crystal structure studies. In the present study, the effects of lattice solvent and substitution of halogens on the pyridine ligand to the valence tautomerism are demonstrated in cobalt bis(dioxolene) molecular complexes. Abstract : A variable‐temperature single‐crystal structural study of five valence tautomeric cobalt molecular complexes, Co II (3, 5‐DBSQ)2 (DBPy)2 (1), Co II (3, 5‐DBSQ)2 (DBPy)2 ·1.33C7 H8 (1 S ), Co II (3, 5‐DBSQ)2 (DCPy)2 ·C7 H8 (2 S ), Co II (3, 5‐DBSQ)2 (TBPy)2 (3) and Co II (3, 5‐DBSQ)2 (TCPy)2 (4) (S = toluene, 3, 5‐DBSQ = 3, 5‐di‐ tert ‐butylsemiquinonate, DBPy = 3, 5‐dibromopyridine, DCPy = 3, 5‐dichloropyridine, TBPy = 3, 4, 5‐tribromopyridine and TCPy = 3, 4, 5‐trichloropyridine) is reported. The re‐crystallization of (1 S ) in toluene at 277 K resulted in a concomitant formation of a solvent‐free polymorph, Co II (3, 5‐DBSQ)2 (DBPy)2 (1). Thermally induced valence tautomerism (VT) is observed only in (1 S ), (1) and (2 S ) [hs‐Co II (3, 5‐DBSQ)2 L2 ↔ ls‐Co III (3, 5‐DBSQ)(3, 5‐DBCat)L2 (hs = high spin, ls = low spin, 3, 5‐DBCat = 3, 5‐di‐ tert ‐butylcatecholate)], whereas (3) and (4) remain locked in the hs‐Co II (3, 5‐DBSQ)2 state during cooling of the sample. Multi‐temperature single‐crystal studies demonstrate the change in cobalt coordination environment during the VT conversion. The non‐solvated compound (1) shows a sharp VT transition ( T 1/2 ∼ 245 K with Δ T ∼ 10 K) from hs‐Co II (3, 5‐DBSQ)2 (DBPy)2 to ls‐Co III (3, 5‐DBSQ)(3, 5‐DBCat)(DBPy)2 oxidation state, whereas the other polymorph with lattice solvent (1 S ) results in a broad transition ( T 1/2 ∼ 150 K with Δ T ∼ 100 K). This increase in the VT transition temperature for (1) relative to (1 S ) illustrates the effect of lattice solvent on the VT transition mechanism. Additionally, the influence of halogen substitutions on the pyridine ring is discussed with respect to observed VT behaviour in the studied compounds.